Ajaran Agama Hindu Dalam Geguritan Candrabherawa Sebagai Penguatan Pendidikan Karakter - I Wayan Agus Gunada (Kamaya: Jurnal Ilmu Agama, 2020)
Literary works are not merely a bouquet made in a short period of time, but are made with the various components and elements that make a literary work so much appreciated. Bali also in its development also has so many heritages of traditional and modern literary works but which generally become a historical heritage containing so many sacred Hindu religious teachings and still so highly developed in Bali is a rash. The Geguritan as mentioned by experts is a traditional literary heritage in which there are elements of Hindu religion that becomes one of the media in conveying Hindu teachings. One of the most well-known rash is Candrabherawa, composed and composed by I Ketut Ruma which tells the story of the War of Hastinapura with Dewantara due to differences in the implementation of religious teachings. So, of course, there are profound philosophical teachings. The study of the rash of Candrabherawa texts emphasizes the study of the value of Hindu teachings contained in the rash text. From the results of the study, that the text of Candrabherawa is the teaching of Tri Hita Karana, Tri Kaya Parisudha, Catur Marga, and chess clan that can be a reference and guidance in implementing the internalization of Susila value on the strengthening of character education for students by education actors in education institutions.